Ion channel regulation by phosphorylation - Shipston, Mike (Henry Stewart Talks, 2011)
Overview of ion channel phosphorylation, Regulation via phosphorylation of ion channel pore forming subunits, Channel regulation by dephosphorylation, Conditional regulation: posttranscriptional and posttranslational crosstalk, Channels and phosphorylation signalling complexes, Ion channel regulation via phosphorylation of signalling complexes, Control of channel trafficking and expression by phosphorylation, Diseases due to aberrant ion channel phosphorylation, Future challenges